Evaluation of the Early Detection of Child Growth and Development Program (DDTK) at RA Bani Adam, Bekasi City: An Evaluation Study Using the CIPP Model - Cindhy Kurnia Amalia; Chandra Apriyansyah; Sukiman Sukiman (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to evaluate the implementation of the Early Detection of Child Growth and Development Program (DDTK) at RA Bani Adam, Bekasi City using the CIPP model (context, input, process, product). The study used a descriptive qualitative approach with data sources from the principal, teachers, parents, activity observations, and program documentation. Data collection was conducted through in-depth interviews, participatory observation, and documentation studies, then analyzed using the Miles and Huberman model. The results of the study indicate that in the context aspect, the DDTK program was born from the institution's real need for objective data on child development and is aligned with the direction of SDIDTK, but is not yet supported by written SOPs. In the input aspect, the school has basic anthropometric tools and support from collaboration with the community health center, but the number of tools is limited, teachers have not received formal training, and screening instruments are not yet available independently. In the process aspect, physical measurements have been conducted monthly but not consistently across all classes, recording is still manual, and follow-up is not systematically scheduled. In the product aspect, the program helps detect delays, strengthens school-parent communication, and triggers early referrals, but longitudinal analysis and documentation of intervention results are not optimal. Overall, the DDTK program at RA Bani Adam is relevant and beneficial, but requires strengthening of standardization, teacher training, data integration, and sustainable follow-up to be more effective and sustainable.